High-Efficiency Bridgeless Resonant Converter for Street LED Lighting Application - Navid Molavi; Shirin Askari; Hosein Farzanehfard; Hani Vahedi (IEEE Open Journal of Power Electronics)
A novel single-stage LED driver for street lighting application is proposed in this article which combines a totem-pole boost PFC and a non-isolated LCCL resonant network. The converter offers several benefits, including: appropriate total harmonic distortion (THD) level and high power factor (PF) of the input current; reduced conduction losses and suppressed electromagnetic interference (EMI) thanks to its bridgeless structure; zero-voltage switching (ZVS) for the main switches and zero-current switching (ZCS) for rectifier diodes across the entire input voltage range and load conditions; a constant output current to an LED string load due to the LCCL network characteristic at the resonant frequency; and fixed-frequency operation via the main switches duty cycle for regulating the output current. The paper provides a detailed explanation of the proposed driver operating modes and theoretical analysis, as well as a comprehensive analysis of the impact of parameters on DC-link voltage level and main switches voltage stress. A design procedure is also presented. Experimental verification is demonstrated through a 100W prototype circuit operating at 200 kHz.